Habits and Envy: What Drives the Consumption Behavior of U.S. Households? Evidence from PSID, 1999-2009 - Kai D. Schmid; Moritz Drechsel-Grau (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2013)
In this paper we estimate the relevance of habits versus interpersonal comparisons for the consumption behavior of U.S. households. We exploit information from the recently released consumption expenditure data of the Panel Study of Income Dynamics (PSID) covering the time span from 1999 to 2009. We find that both habits, measured as lagged consumption, and envy motives, measured as reactions of consumption to consumption changes of households that are perceived to be richer, matter substantially. Hence, household consumption is not only determined by habit persistence but also by interpersonal comparisons. Most importantly, our estimations reveal that envy motives might play a much more prominent role for households' consumption choices than habits do.
urn:nbn:de:101:1-2014031110232
Keywords: C23; D12; D91; E21; 330; Household Consumption; Reference Consumption; Habits; Relative Income Hypothesis; Difference GMM; PSID